2018
DOI: 10.1007/s41463-018-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Networks or Structures? Organizing Cultural Routes Around Heritage Values. Case Studies from Poland

Abstract: The most common way of managing cultural heritage recently takes form of cultural routes as they seem to offer a new model of participation in culture to their recipients; they are often a peculiar anchor point for inhabitants to let them understand their identity and form the future; they offer actual tours to enter into interaction with culture and history, to build together that creation of the heritage, which so is becoming not only a touristic product, but, first of all, the space for cultural, social and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Contemporary heritage theorists evoke the need to adopt an integrated approach to the issue of cultural heritage, focusing on its social and economic impact on the sustainable development of regions and examining the networks and ecosystems that they create [25][26][27]. In the course of these reflections, the idea of cultural routes was born, at first as a local grassroots initiative that, in time, grew to an international scale.…”
Section: Cultural Routes As An Example Of Sustainable Heritage Managementioning
confidence: 99%
See 4 more Smart Citations
“…Contemporary heritage theorists evoke the need to adopt an integrated approach to the issue of cultural heritage, focusing on its social and economic impact on the sustainable development of regions and examining the networks and ecosystems that they create [25][26][27]. In the course of these reflections, the idea of cultural routes was born, at first as a local grassroots initiative that, in time, grew to an international scale.…”
Section: Cultural Routes As An Example Of Sustainable Heritage Managementioning
confidence: 99%
“…The basic premise of this study was to treat the route as a network structure that is formulated by a wide group of its participants and stakeholders, in accordance with the belief that the basic reference group for the functioning of the route comprises those who remain in its immediate environment (residents) and, rarely, entities appearing in its area occasionally, and sometimes only once (tourists). An important reference point was also the research that was conducted by Bogacz-Wojtanowska and Góral [25], which showed that the structures that were adopted by cultural routes vary, starting from network relations that are fragmentary and under development, to very loose, bottom-up networks, to formalised and hierarchical permanent sites. In their research, Bogacz-Wojtanowska and Góral [25] emphasised that the type of the adopted route structure (loose, built at the grassroots level on the basis of relations between people, or more formalised, with top-down construction and management) has a significant impact on how a route is organised and how it develops.…”
Section: Cultural Routes As An Example Of Sustainable Heritage Managementioning
confidence: 99%
See 3 more Smart Citations